Perancangan Kampung Tematik Jajan Pasar Gajahmungkur sebagai Destinasi Wisata - Anisa Feritrianti; Riska Amelia Dewi; Wakhidah Kurniawati; Santy Paulla Dewi; Nurini Nurini; Diah Intan Kusumo Dewi (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2022)
Kampung Tematik (Thematic Village) is an area in the village that shows the community’s identity. It shows the potential local wisdom as a result of community agreement. Thematic Village might be the answer for the problem of basic needs, especially in improving the quality of the living environment of the poor and basic infrastructure by organizing and developing the area based on local and dynamic potential. Kampung Tematik Jajan Pasar Gajahmungkur is one of the thematic villages located in the Gajahmungkur Sub District. This idea was initiated by local communities who understand the potential of the home industry. Therefore, it is necessary to support a city concept to make thematic kampung into tourist destinations. The purpose of this study is to provide concept and design recommendations for the development of thematic kampung as a tourist destination. Data collection methods used are field observation, interviews, institutional surveys, and review documents. The result of the study is the concept and design recommendations which are expected to be one of the inputs and considerations for the city government policies in relation to the development of thematic kampung into tourist destinations.